2000
DOI: 10.1089/10799900050163226
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of IFN-β1a in Healthy Volunteers

Abstract: The pharmacokinetics of recombinant human interferon-beta1a (IFN-beta1a) (Rebif, Ares-Serono, Geneva, Switzerland) were investigated in healthy volunteers following intravenous (i.v.) administration of increasing single doses of the drug (22 microg/6 million international units [MIU], 44 microg/12 MIU, and 66 microg/18 MIU); i.v., intramuscular (i.m.), and subcutaneous (s.c.) administration of a 66-microg dose; and repeated s.c. administration of four 66-microg doses at 48-h intervals. The disposition of IFN-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 40 publications
9
75
0
2
Order By: Relevance
“…4. The overall profiles demonstrate a delayed onset and slow return toward baseline, which is qualitatively similar to the response observed in humans (Buchwalder et al, 2000).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…4. The overall profiles demonstrate a delayed onset and slow return toward baseline, which is qualitatively similar to the response observed in humans (Buchwalder et al, 2000).…”
Section: Resultssupporting
confidence: 72%
“…This is consistent with the relatively large size of IFN-␤1a and, with the exception of specific and nonspecific binding, the compound jpet.aspetjournals.org should mostly reside in the plasma. Although this study was conducted in monkeys, the metabolism and elimination of interferons are similar across most species (Gloff and Wills, 1992), and the model has been shown to be relevant in humans (Buchwalder et al, 2000;Mager and Jusko, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…25 It also is a potent inhibitor of proliferation for many cancer cells in vitro. 18,19 However, it cannot be used effectively as cancer therapy because the maximum tolerated dose is not high enough to attain these effects when given systemically [26][27][28] and it has a short half-life. Although it has been shown that serum levels of interferon delivered by engineered stem cells are insignificant in contrast to interferon given systemically, 15 the local production of IFN-b appears to be the key for tumor growth attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our findings support the clinical attractiveness to use IFN-h in the treatment of GEP-NETs, considering that IFN-h inhibited cell proliferation and stimulated apoptosis already at very low concentrations (1-10 IU/mL). These concentrations can be achieved in vivo because 12.3 IU/mL is the maximal IFN-h serum concentration reported in healthy subjects after s.c. administration of this cytokine (47,48). Translation of these findings into a clinical application is, however, not easy, considering the short half-life of IFN-h.…”
Section: Discussionmentioning
confidence: 99%